Enhanced electrical and broad spectral (UV-Vis-NIR) photodetection in a Gr/ReSe2/Gr heterojunction. Issue 29 (9th July 2020) - Elahi, Ehsan; Khan, Muhammad Farooq; Rehman, Shania; Khalil, H. M. Waseem; Rehman, Malik Abdul; Kim, Deok-kee; Kim, Honggyun; Khan, Karim; Shahzad, Moazzam; Iqbal, Muhammad Waqas; Basit, Muhammad Abdul; Khan, Fasihullah
Abstract : Excellent electrical and photoelectrical study of vertical integration by layered two-dimensional materials having gate tunable broad spectral (UV-Vis-NIR) light detection response. Abstract : Vertical integration of two dimensional (2D) layered materials is indispensable in making van der Waals (vdWs) heterostructures for promising electronic and optoelectronic devices. Herein, we report excellent electrical and photoelectrical measurements where the current ON & OFF ratio of FET is increased by decreasing the temperature in the graphene/ReSe2 /graphene heterojunction. We investigated the photoresponsivity in broad spectral range (UV-Vis-NIR) and achieved high photoresponsivity of 1.5 × 10 7 A W −1 and external quantum efficiency of ∼64% at λ = 220 nm. Further, the photovoltaic effect was examined, which significantly modulated the short circuit current ( I sc ) from 4.2 × 10 −8 A to 2.6 × 10 −7 A and open-circuit voltage ( V oc ) from 0.21 V to 0.44 V at different wavelengths (1064, 840, 514 and 220 nm), attributed to the photo-generation and recombination rate of the carriers. Moreover, photoresponsivity was observed near 1.2 × 10 6, 8.6 × 10 6 and 1.5 × 10 7 A W −1 by applying different gate biases (0, 20 and 40 V), respectively. Further, we have explored the photocurrent and photoresponsivity at different intensities of incident light (200, 260, 400, 620 and 850 μW cm −2 ). In addition, we calculated the rise and decay response times of photodetectors at different wavelengths and power densities, which depend upon the trap sites in the energy band of ReSe2 . These devices opened up new ways to improve the performance of photodetectors from the UV to the NIR region.